Impact of printing surfaces with UV-curable inks on sound absorption: DOI 10.14622/JPMTR-2003 - Kitanovski, Vlado; Nersveen, Jonny; Strand, Anton; Pedersen, Marius (Journal of Print and Media Technology Research, 2020)
The recent UV-curable inks, used in modern inkjet printing systems, bring several advantages and therefore a potential to expand to new applications, including décor printing. In this work, we investigate the impact of printing with UV-curable inks on sound absorption. The sound absorption curves of three different sound-absorbing decorative wall plates are calculated from the reverberation times measured in a reverberation room. The comparison between the sound absorption from unprinted and printed decorative plates showed that printing with UV-curable inks has no significant impact on the sound absorbing characteristics of materials.